(untitled) (Journal of the College of Basic Education, 2022)
The research aims to prepare special exercises for rubber ropes to correct the deformity of the bow legs. And knowing the effect of exercises (with rubber ropes) in reducing the bowing of the legs of the research sample. And to know the effect of exercises (with rubber ropes) on the strength sensing test. The researcher used the experimental method (one group) with two tests, before and after, for its relevance to the nature of the problem on a sample of children with bow legs aged (8-10) years who were reviewed at Al-Wasiti Hospital (Baghdad - Al-Rusafa) for the period from 11/1/2020 until 3/1/ 2021 and their number was (10) selected according to the diagnosis of the specialist doctor (Dr. Abdel Nasser Kamel, specializing in joints and bones in Al-Wasiti Hospital Consultation) through medical examination and radiology (scan gram). Then the tests were applied, and after applying the curriculum for a period of 12 weeks, the researcher used the statistical package (SPSS), to process the data he obtained. In light of the results reached by the researcher, he came to the following conclusions: - The rehabilitation units using rubber ropes have a positive effect in reducing the curvature of the legs, as the results showed significant differences in measuring the curvature of the legs using X-rays. The rehabilitation exercises using rubber ropes have a positive effect on muscular strength, as the results showed significant differences in the strength sensing test.